Status of the EDEN ISS Rack-like food production unit after five months in Antarctica - Boscheri, Giorgio; Marchitelli, Giovanni; Volponi, Marco; Zabel, Paul (2018)
Plant cultivation in large-scale closed environments is challenging and several key technologies necessary for space-based plant production are not yet space-qualified or remain in early stages of development. The Horizon2020 EDEN ISS project aims at development and demonstration of higher plant cultivation technologies, suitable for near term deployment on the International Space Station (ISS) and from a long-term perspective, within Moon and Mars habitats. The EDEN ISS consortium, as part of the performed activities, has designed and built a plant cultivation system to have form, fit and function of an European Drawer Rack 2 (EDR II) payload, with a modularity that would allow its incremental installation in the ISS homonymous rack, occupying from one-quarter rack to the full system. The developed system has been completed and tested in a laboratory environment in early 2017. The system was then integrated and tested at DLR Bremen into the main transport container (MTF). In the last 5 months the system was operated also in the highly-isolated German Antarctic Neumayer Station III, in the container-sized test facility to provide realistic mass flow relationships and interaction with a crewed environment. This paper describes the key results of the Bremen test phase as well as initial ISPR plant growth facility tests in Antarctica as space-analogue environment.